2013
DOI: 10.1177/0972150912466445
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Indian Index Funds

Abstract: An index fund is a mutual fund that aims to imitate some benchmark index. There are several advantages of investing in an index fund, namely, exposure to a diversified portfolio, minimization of company-specific risks, high liquidity, etc. In India, there has been a significant growth in the number of index funds from 2002 onwards. Today there are more than 20 index funds imitating the NIFTY or SENSEX. In this article, we review and compare a number of Indian index funds. The CRISIL composite ranking of an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Since an index fund aims to replicate a market index, it is natural to expect the fund to have similar market risk and returns as the index that it imitates. However, from Sarkar et al (2013), we see that not all the Indian index funds perform equally well in terms of following a benchmark index closely over a long period of time. The goal of this article is to assess whether the index funds imitating S&P BSE SENSEX or the CNX NIFTY indices exhibit similar market risk as that of the SENSEX or NIFTY index?…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Since an index fund aims to replicate a market index, it is natural to expect the fund to have similar market risk and returns as the index that it imitates. However, from Sarkar et al (2013), we see that not all the Indian index funds perform equally well in terms of following a benchmark index closely over a long period of time. The goal of this article is to assess whether the index funds imitating S&P BSE SENSEX or the CNX NIFTY indices exhibit similar market risk as that of the SENSEX or NIFTY index?…”
Section: Introductionmentioning
confidence: 91%
“…Athma and Mamatha (2012) have observed that there has been a significant growth of the index funds since their inception. A well-known measure of the performance of an index fund is the tracking error, which is usually defined as the annualized standard deviation of the difference between the daily returns of the index funds and the target index (see Sarkar et al (2013)). Fernandes (2003) has pointed out that the tracking error of an index fund can be highly sensitive to the market volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The main alternative investing opportunities include hedge funds and funds of hedge funds, venture capital funds and private equity (see Exhibit 1). Traditional investment opportunities are based on the assumption that fund managers will try to enhance the value of fund by continuous efforts and monitoring (Sarkar, Dutta & Dutta, 2013). So is the assumption of alternate investment opportunities.…”
Section: Introductionmentioning
confidence: 99%